Simple and Truly Nonsingular Direct Formulation for Boundary Element Analysis of Elastostatic and Plate Bending Problems - Sasikala, D.; Ameen, M. (Journal of Structural Engineering, 2025)
A simple and truly nonsingular direct formulation for the boundary element analysis of elastostatic and plate bending problems is addressed in this paper. Regularised boundary integral equation for elastostatic problem is obtained by utilising a uniform displacement field and a uniform stress field. For the plate bending problem, the strongly singular and hypersingular integral terms are regularised by applying uniform deflection and uniform deflection gradient fields. The effectiveness of the proposed method is demonstrated with numerical examples. The results are seen to compare well with known results.